Ferritins as Nanoplatforms for Imaging and Drug Delivery - Zhen, Zipeng (Expert Opin Drug Deliv, 2014)
INTRODUCTION: Due to unique architecture and surface properties, ferritin has emerged as an important class of biomaterial. Many studies suggest that ferritin and its derivatives hold great potential in a wide range of bio-applications. AREAS COVERED: In this review, we summarize recent progress on employing ferritins as a platform to construct functional nanoparticles for applications in magnetic resonance imaging (MRI), optical imaging, cell tracking, and drug delivery. EXPERT OPINION: As a natural polymer, ferritins afford advantages such as high biocompatibility, good biodegradability, and a relatively long plasma half-life. These attributes put ferritins ahead of conventional materials in clinical translation for imaging and drug delivery purposes.